Pengaruh Ukuran Perusahaan, ROA, DAR, Dan Reputasi Auditor terhadap Audit Delay - Mimelientesa Irman (COSTING : Journal of Economic, Business and Accounting, 2017)
This study aims to analyze the factors that affect audit delay on manufacturing companies listed in Indonesia Stock Exchange. This test uses multiple linear regression model. Sample of this study are 20 companies in manufacturing sector. Observation period is 6 years from 2010 to 2015. Independent variables in this study consisted of company size, profitability, solvency, and auditors reputation which tested its influence on audit delay as dependent variable. The results showed that company size, profitability, solvency, and auditors reputation significantly influence on audit delay of manufacturing companies listed in Indonesia Stock Exchange period 2010 until 2015 Keywords: Firm size, ROA, DAR, Reputation Auditor and Audit Delay